Treinamento de corrida de endurance baseado na variabilidade da frequência cardíaca em mulheres não treinadas: efeitos sobre a performance - Silva, Danilo Fernandes da (2016)
The peak speed (Vpeak) is a variable capable of predict running endurance performance and if associated with its time limit (tlim) may be used as a parameter for running training prescription. Besides the variables related to training prescription, it is also necessary to use parameters that are useful for controlling the adequate exercise intensity to be prescribed as well as the possible physiological adaptations associated with training. Within the possibilities, the heart rate variability (HRV), used to indicate parasympathetic nervous system activity, has been applied to make the decisions related to training prescription. Psychological variables are also recommended to complement training control, as well as its effects. Thus, the aim of the present study was to analyze the use of HRV to control training intensity of eight weeks of endurance running training in young untrained women. Thirty women aged 18 to 35 years took part of the study, who were randomized in two groups of 15 women each. The control group (CG) performed training based on a conventional training prescription whereas the other group performed the running training based on parasympathetic nervous system activity (i.e., index rMSSD of HRV) (GHRV). The participants undertook anthropometric assessment, questionnaires to assess dietary pattern, psychological variables (stress, recovery and mood profile), and symptoms related to pre-menstrual syndrome, autonomic modulation (i.e., HRV at rest and heart rate recovery after maximal exercise), physical tests on the treadmill and running performance in a track. It was conducted two tests in the treadmill: an incremental test to determine Vpeak and another one to determine its tlim and the time to complete 5-km running performance (t5km) in a 400-m oficial running track. All the baseline evaluations were performed before (week 1) and after a period of four (week 6) and eight (week 11) of training. The participants performed at least 90% of the 24 training sessions (i.e., three sessions per week) subdivided in moderate intensity continuous training and high intensity interval training. The analysis of variance and effect sizes (ES) were calculated to verify the adaptations to training. The main findings were that the t5km reduced significantly from week 1 to week 11 in both groups (CG = 35.5 ± 5.0 min to 30.5 ± 4.3 min, HRVG = 36.3 ± 4.5 min to 29.8 ± 2.4 min); however, in a greater magnitude in HRVG (ES = large) than in CG (ES = moderate) (ES between-group difference = moderate). The Vpeak also significantly improved in both groups (CG = 11.0 ± 1.4 km·h-1 to 11.9 ± 1.4 km·h-1, HRVG = 10.9 ± 1.2 km·h-1 to 11.9 ± 0.9 km·h-1), with a moderate ES within-group for both groups and a small ES between-group. The tlim at Vpeak increased only in HRVG (5.1 ± 1.3 min to 6.1 ± 1.7 min), with a moderate ES for the between-group differences. In addition, the parasympathetic indexes of HRV at rest improved in HRVG (30.5 ± 9.9 ms to 37.5 ± 13.2 ms and 22 ± 6.9 to 26.7 ± 9.4, respectively) and did not present statiscally significant differences in the CG (ES between-group differences = small for rMSSD and trivial to SD1). The index SD2 increased only in HRVG (77.8 ± 16.3 to 93.6 ± 22.1) with a moderate ES within- and between-groups. The variable representing parasympathetic reactivation (i.e., heart rate recovery) also improved more in the HRVG compared to the CG (CG = 36.9 ± 7.4 bpm to 41.1 ± 7.6 bpm, HRVG = 36.7 ± 9.7 bpm to 42.7 ± 10.7 bpm, ES between-group differences = small). Although the HRVG has performed less moderate intensity continuous training than the CG, this amount of training presented a negative and moderate correlation with changes in performance (i.e., t5km) (r = -0.44). The CG presented improvements on emotional stress (2.0 ± 1.2 to 1.2 ± 0.9), conflicts/pressure (2.9 ± 1.1 to 2.2 ± 1.0), and recovery related to sleep quality (3.1 ± 1.0 to 4.0 ± 0.8), personal accomplishment (2.8 ± 1.7 to 3.7 ± 1.4), self-regulation (3.3 ± 1.3 to 4.1 ± 1.2), mean specific recovery (3.1 ± 1.2 to 3.7 ± 1.0) and mean total recovery (3.2 ± 0.9 to 3.6 ± 0.9). On the other hand, the HRVG improved general stress (1.6 ± 1.1 to 1.1 ± 0.6), emotional stress (2.0 ± 1.0 to 1.4 ± 0.7), social stress (1.6 ± 1.1 to 0.8 ± 0.5), lack of energy (2.2 ± 1.0 to 1.4 ± 0.8), mean general stress (2.1 ± 0.8 to 1.6 ± 0.4) and self-regulation (3.1 ± 1.0 to 3.9 ± 1.1). Additionally, the HRVG also improved mood state on the scales tension (6.1 ± 5.1 to 3.3 ± 3.2), depression (4.9 ± 4.3 to 2.2 ± 2.1), anger (9.7 ± 3.6 to 6.9 ± 2.9), fatigue (7.9 ± 3.5 to 5.3 ± 2.0) and total mood disturbance (28.5 ± 16.3 to 17.8 ± 6.6). The CG reduced vigour (8.9 ± 3.6 to 6.9 ± 3.0), which was not observed in the HRVG. The variation in Vpeak after training presented a large correlation with the variation in t5km (r = -0.65). It is concluded that 1) the endurance running training based on HRV presented greater improvements in the 5 km performance than the conventional/standardized training program, as well as for the autonomic modulation; 2) The training based on HRV also improved mood profile and stress-related aspects that were not improved in the CG; 3) the percentage variation of Vpeak after training was the one that presented the highest correlation with changes in 5 km performance.